2000
DOI: 10.1182/blood.v96.10.3364.h8003364_3364_3368
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipoprotein (a) levels as an independent risk factor for venous thromboembolism

Abstract: Elevation of serum lipoprotein (a) (Lp[a]) is a known risk factor predisposing to cardiovascular and cerebrovascular disease. However, little is known about the role of increased Lp(a) in venous thromboembolism (VTE). This study evaluated the role of Lp(a) among a panel of established hereditary thrombogenic defects in patients with VTE. A total of 685 consecutive patients with at least one episode of VTE and 266 sex- and age-matched healthy controls were screened with regard to activated protein C resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
2
32
0
3
Order By: Relevance
“…Consistent with our study, several case-control studies have demonstrated an association between concentrations of serum lipids such as TG, TC, and lipoprotein (a) and VTE. [ 31 34 75 76 ] However, a number of large prospective studies have failed to confirm such associations, failing to support a role for serum lipids in the pathogenesis of VTE. [ 10 27 41 49 ] Our study showed that VTE was indeed associated with dyslipidemia; however, a funnel plot and Egger test suggested the presence of publication bias for the association between VTE and TG.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, several case-control studies have demonstrated an association between concentrations of serum lipids such as TG, TC, and lipoprotein (a) and VTE. [ 31 34 75 76 ] However, a number of large prospective studies have failed to confirm such associations, failing to support a role for serum lipids in the pathogenesis of VTE. [ 10 27 41 49 ] Our study showed that VTE was indeed associated with dyslipidemia; however, a funnel plot and Egger test suggested the presence of publication bias for the association between VTE and TG.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, emerging data supports an association between elevated Lp(a) and VTE risk. Several case-control studies have shown increased VTE risk with elevated Lp(a) concentrations [14][15][16][17]. Two meta-analyses of these study designs have also confirmed these associations [18,19].…”
Section: Introductionmentioning
confidence: 92%
“…Several reports based on case-control designs have reported on the associations between circulating Lp(a) and VTE risk. Though the findings from these reports have been mixed, majority have generally shown an increased risk of VTE with elevated Lp(a) [14][15][16][17]. There have also been efforts to aggregate these data resulting in two published reviews on the topic.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…In regard to venous thromboembolism (VTE), von Depka and colleagues analyzed the role of elevated Lp(a) levels (> 30 mg/dL) in a population of 685 patients with at least one episode of VTE, compared with a control group, and discovered elevated Lp(a) levels were found in 20% of all patients, compared with 7% in the control group (P < .001, odds ratio [OR] 3.2, 95% confidence interval [CI] 1.9-5.3) [29]. A recent meta-analysis of 90,904 individuals and 5029 stroke events found an association with Lp(a) when comparing high and low Lp(a) levels and revealed an estimated OR of 1.41 (95% CI, 1.26-1.57) for case-control studies and an estimated RR of 1.29 (95% CI, 1.06-1.58) for prospective trials [30].…”
Section: Lp(a) and Antifibrinolytic Effectsmentioning
confidence: 99%